Enhancement of the growth of human endothelial cells by surface roughness at nanometer scale - Chung, Tze-Wen; Liu, Der-Zen; Wang, Sin-Ya; Wang, Shoei-Shen (Biomaterials, 2003)
This study investigated whether a nanometer scale of surface roughness could improve the adhesion and growth of human endothelial cells on a biomaterial surface. Different molecular weights or chain lengths of polyethylene glycol (PEG) were mixed and then grafted to a polyurethane (PU) surface, a model smooth surface, to form a nanometer (nm) scale of roughness for PU-PEG surfaces (PU-PEG mix) while PEG with a molecular weight of 2000 was also grafted to PU to form PU-PEG 2000 for comparison. In addition, the concept was tested on cell-adhesive peptide Gly–Arg–Gly–Asp (GRGD) that was photochemically grafted to PU-PEG mix and PU-PEG 2000 surfaces (e.g., PU-PEG mix-GRGD and PU-PEG 2000-GRGD surfaces, respectively). To prepare GRGD-grafted PU-PEG mix and PU-PEG 2000 surface, 0.025 m of GRGD-SANPAH ( N-Succinimidyl-6-[4′-azido-2′-nitrophenylamino]-hexanoate) solutions was grafted to PU-PEG mix and PU-PEG 2000 by surface adsorption of the peptide and subsequent ultraviolet (UV) irradiation for photoreaction. The grafting efficiencies for GRGD to PU-PEG mix and PU-PEG 2000 surfaces were about 67% for both surfaces, semi-quantitatively analyzed by an HPLC. The surface roughness, presented with a roughness parameter, R a, and the topography of the tested surfaces were both measured and imaged by an atomic force microscope (AFM). Among the R a values of the films, PU was the smoothest (e.g., R a=1.53±0.20 nm, n=3) while PU-PEG mix was the roughest (e.g., R a=39.79±10.48 nm, n=4). Moreover, R a values for PU-PEG mix and PU-PEG mix-GRGD surfaces were about 20 nm larger than those for PU-PEG 2000 and PU-PEG 2000-GRGD, respectively, which were consistent with the topographies of the films. Human umbilical vein endothelial cells (HUVECs) were adhered and grown on the tested surfaces after 36 h of incubation. Among the films, HUVEC's adhesion on the surface of PU-PEG mix-GRGD was the densest while that on the surface of PU-PEG 2000 was the sparsest. Also, the adhesion and growth of HUVECs for the roughness surfaces were statistically significantly better than that of smooth surface for both GRGD grafted and un-grafted surfaces, respectively. The viability for the growth of HUVECs on the tested surfaces analyzed by MTT assay also confirmed the efficacy of the increased surface roughness. In conclusion, increased surface roughness of biomaterial surfaces even at 10–10 2 nm scale could enhance the adhesion and growth of HUVECs on roughness surfaces that could be useful for applications of tissue engineering.